ANALISIS BAURAN KOMUNIKASI PEMASARAN PADA KOPI KAWA - Sari, Devi Puspita; Pratiwi, Aprilyanti (Jurnal Insani, 2023)
In the modern era, the development of the culinary industry has increased, with the widespread presence of coffee shops in various parts of Indonesia. This phenomenon makes a great opportunity for business people, with the presence of coffee shops making a new habit in society and providing many choices for products to be consumed. So that this becomes a tight competition for coffee shop business actors to carry out various strategies to maintain consumer buying interest. The problem in this study is how the implementation of the marketing communication mix at Kopi Kawa. The research objective is to analyze the marketing communication mix of Kopi Kawa. The concepts used are marketing communication and marketing communication mix. This research uses a post positivism paradigm with a descriptive qualitative approach. The unit of analysis is an organization that is included in a large scale, namely a coffee shop. Data collection techniques using interviews and documentation. This research uses data analysis techniques, namely data reduction, data presentation and conclusion drawing. The results showed that Kopi Kawa implemented marketing communication by combining eight elements of the marketing communication mix. Other findings reveal that the most dominant marketing communication mix used is sales promotion and word of mouth.